Association between estimated glucose disposal rate and the risk of atherosclerotic cardiovascular disease: insight from cross-sectional and retrospective cohort studies - Wang, Zixuan; Zhou, Qingyun; Zheng, Tao; Huang, Taotao; Yi, Kefan (Frontiers in Nutrition, 2025)
BackgroundAccumulating data have elucidated a significant association between insulin resistance (IR) and the risk of cardiovascular diseases. The estimated glucose disposal rate (eGDR), a quantitative indicator of glucose metabolism, has been increasingly recognized as a reliable clinical indicator of IR. Atherosclerotic cardiovascular disease (ASCVD) is a type of cardiovascular disease caused by atherosclerosis. However, the association and potential mechanisms between eGDR and ASCVD risk remain unclear.MethodsWe conducted cross-sectional and retrospective cohort studies using data from the two health examination centers of Qingdao University Affiliated Shanghai Deji Hospital and Ningbo Medical Center Lihuili Hospital to horizontally and longitudinally evaluate the potential relationship and explore potential mechanisms between eGDR and the risk of ASCVD.ResultsA significant negative linear association between eGDR and ASCVD risk was observed in our study. After adjusting for some covariates, each unit increment in eGDR was associated with a 16.1% decrease in odds ratio of ASCVD (OR = 0.839, 95% CI: 0.806–0.894) in the cross-sectional study and a 12.4% decrease in hazard ratio of ASCVD (HR = 0.876, 95% CI: 0.788, 0.974) in the retrospective cohort study. This negative association was robust in most subgroups and various sensitivity analyses. Furthermore, eGDR presented greater predictive performances for ASCVD diagnosis and new-onset ASCVD risk compared with TyG, HOMA-IR, and METS-IR. In addition, AIP, VAI, CMI, LAP, and BMI had partial mediation effects on the association between eGDR and ASCVD risk.ConclusionThis study elucidates the significant negative dose-response linear relationship of eGDR with ASCVD risk and the partial mediation effects of AIP, VAI, CMI, LAP, and BMI, highlighting the significance of enhancing glucose-utilizing capacity in decreasing the risk of ASCVD.